The Effect of International Security Dynamics on Asia Pacific Regionalism - Ryan Dhanu Umboh (Research Synergy Foundation, 2022)
This article explains the emerging security dynamics in the Asia-Pacific toward the effect of the increase of international security of Asia Pacific country and this research also depicted the contribution of regional organization such as ASEAN, East Asian country and Atlantic country. Even though the relations of ASEAN Country with East Asian Country still strong, this research elucidated the relations which build stronger through transfer of technology toward each other. This is qualitative research which were adopted in-depth interview to gain data and processed with coding technique. The informant was an expertise in the field who has served the institution for more than 10 years. The results show that This forum is the only forum in the world that is able to bring together regional countries and relevant international organizations to discuss issues of people smuggling and trafficking in persons and other transnational crimes. This forum also discusses the interests of countries of origin, transit countries and also destination countries.